Rationality in the Qur'an: Integrating Reason and Revelation for Contemporary Islamic Education - Bhat, Ali Muhammad; Bisati, Afroz Ahmad (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Scholars explore the concept of rationality from various angles, often associating it with thinking that transcends divine considerations. In these debates, some academics have positioned themselves against the Quran, questioning its consistency with rational thought—however, many scholars argue that the Quran addresses subjects metaphysically, harmonizing reason and revelation. A detailed examination reveals numerous verses advocating reasoning, critical thinking, and empirical analysis. These verses invite believers to reflect on natural phenomena, historical events, and ethical dilemmas, underscoring the Quran's emphasis on intellectual engagement and moral discernment. This paper elucidates the Quran's nuanced approach to rationality by analyzing over five dozen Quranic verses that directly or indirectly discuss the nature and application of reason. Using Islamic research methodologies, it highlights the balance between reason and spirituality, showing that rational thinking is integral to Quranic teachings. This study addresses skeptical or misleading criticisms, affirming that the Quran integrates reason and revelation to offer a comprehensive intellectual and spiritual development framework. Future research should examine how Quranic rationality informs contemporary Islamic thought and practice, especially concerning modern scientific and ethical challenges. Comparative studies between Quranic perspectives on rationality and other philosophical or religious traditions are also recommended to foster interfaith and intercultural understanding.